Identification of protein interaction antagonists using the repressed transactivator two-hybrid system. (May 2007) - Joshi, Phalgun B.; Hirst, Martin; Malcolm, Tom; Parent, Jennifer; Mitchell, David; Lund, Karen; Sadowski, Ivan
The repressed transactivator (RTA) yeast two-hybrid system was developed to enable genetic identification of interactions with transcriptional activator proteins. We have devised modifications of this system that enable its use in screening for inhibitors of protein interactions from small molecule compound libraries. We show that inhibition of protein interactions can be measured by monitoring growth in selective medium containing 3-aminotriazole (3-AT) and using this assay have identified inhibitors of four independent protein interactions in screens with a 23, 000 small molecule compound library. Compounds found to inhibit one of the tested interactions between FKBP12 and the transforming growth factor β receptor (TGFβ-R) were validated in vivo and found to inhibit calcineurin-dependent signaling in T cells. One of these compounds was also found to cause elevated basal expression of a TGFβ-R/SMAD-dependent reporter gene. These results demonstrate the capability of the RTA small molecule screening assay for discovery of potentially novel therapeutic compounds.